2012
DOI: 10.1111/j.1479-8425.2012.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of four established questionnaires to identify highway bus drivers at risk for obstructive sleep apnea in Turkey

Abstract: In Turkey, all heavy‐vehicle driver's license applicants older than 45 years and with body mass index (BMI) >25 kg/m2 are required to have polysomnography (PSG). However, this law is usually overlooked in practice due to the large number of applications. We aimed to assess the usefulness of four standardized questionnaires: Berlin, STOP, STOP‐BANG and OSA50, in identifying the high‐risk bus drivers for obstructive sleep apnea (OSA). Ninety highway bus drivers underwent polysomnography and completed four questi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0
11

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(62 citation statements)
references
References 14 publications
1
50
0
11
Order By: Relevance
“…The results were reported in our previous publication. 3 The sensitivity, specificity, PPV and NPV were 89.1%, 76.9%, 82%, and 85.7% for RDI > 15, respectively. The specificity was 10% and sensitivity 96% for RDI > 5 ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…The results were reported in our previous publication. 3 The sensitivity, specificity, PPV and NPV were 89.1%, 76.9%, 82%, and 85.7% for RDI > 15, respectively. The specificity was 10% and sensitivity 96% for RDI > 5 ( Table 1).…”
Section: Resultsmentioning
confidence: 98%
“…3 As a second procedure, the Watch-PAT 200 can be used to evaluate OSA in those drivers with high risk for OSA with 89.1% sensitivity (Figure 4). Low risk drivers (according to the STOP-BANG questionnaire) had a prevalence of 24% of RDI > 15, with 83% sensitivity and 84% specificity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OSA50 questionnaire involves four components including age ≥ 50, snoring, witnessed apneas and waist circumference. 81 A study involving Turkish bus drivers 82 and a validation study for the OSA50 in the primary care setting 81 showed a sensitivity ranging from 0.49-0.98 and a specificity of 0.82 in both studies (see supplemental material, Table S32 and Table S33). …”
Section: Multivariable Apnea Prediction Questionnairementioning
confidence: 99%
“…Além disso, prevenir a obesidade é uma forma de evitar outros agravos que afligem esta população, tais como mostraram os estudos que encontraram associação da obesidade em rodoviários com índice de distorção respiratória (HUI et al, 2002;HUI et al, 2006); ocorrência de acidentes de trânsito e sono ao dirigir (VIEGAS; OLIVEIRA, 2006); hipertensão arterial sistêmica (BENVEGNÚ et al, 2008;KAEWBOONCHOO et al, 2007;MARCINKIEWICZ;SZOSL AND, 2010;SHIN et al, 2013;LAKSHMAN et al, 2014;ASSUNÇÃO, 2015); hiperglicemia (MARCINKIEWICZ; SZOSLAND, 2010); aumento do nível de chumbo no sangue (KAEWBOONCHOO et al, 2010); insônia e apneia do sono (RAZMPA; NIAT; SAEDI, 2011;FIRAT et al, 2012); adoção de comportamento não saudável de controle de peso (ESCOTO; FRENCH, 2012); sintomas musculoesqueléticos (FERNÁNDEZ-D'POOL et al, 2012); sonolência (SANTOS et al, 2013).…”
Section: Prevalências Da Obesidade Caracterização Da População E Dosunclassified